The peculiarities of pedagogical search of gifted seniors - Maryna Melnyk (Vasyl Stefanyk Precarpathian National University, 2017)
The author examines the question of identification of high school students as gifted.Discusses the psychological and pedagogical criteria of giftedness. The results of an empiricalstudy of gifted high school students search for pedagogical criteria are presented. Key words: giftedness, gifted students, criterion of giftedness.